Nietzsche, genealogical interpretation - Mejía, Jorge Mario (Estudios de Filosofía, 1990)
In the treatise "What is the Meaning of Ascetic Ideals?" Nietzsche develops the genealogy of "the system of interpretation that has best been developed to its ultimate consequences" (Genealogy of Morals, ID, 23). The essay appears as a description of genealogical interpretation in its immanent articulation, and deals, in the last analysis, with the question as to why the modero representatives of that system of interpretation are its alleged antagonists in so far as they renounce to interpret. The posing of the problem is not achieved through a descriptive approach. The background of the essay is the question of the possibility of a non-interpretative description.